Comparative Study of Civil Liability of Building Builders in Islamic Law and Legal Systems of Roman-German Law & Common Law - jamshid mirzaei (پژوهش تطبیقی حقوق اسلام و غرب, 2017)
The development of today's human needs and the remarkable progress of knowledge and the construction industry have made the legal relationships between the two groups of owners and building makers more tense and more complex, and along with the ease and prosperity of public life and residence in luxurious buildings, creates High dangers and duplicate responsibilities. A look at the damage caused by the work of designers, architects, supervisors, engineers and construction executives of small and large projects shows that the failure to observe the necessary standards in one side and efforts for gaining more profits, in the other side, puts the builders in trouble and ignorance and has caused damage to owners , And for this reason, contemporary legal systems have put on the protection of the lost as one of the most important tasks on the agenda and in various ways seeks to find the proper solution and formulate binding rules and effective regulatory steps have been taken in this respect. But there is always this ambiguity that What is the type and basis of civil liability of building builders and to what extent this responsibility is capable of compensating for damage. The fact is that in this area there is no significant difference in the law of the unity of thought and the established framework in the legislative system of countries and legal doctrine. Some of the discussed systems names the responsibility (guarantee) and its basis the risk theory, and some others believe that creators have strict and sole responsibility and some proportionate to the amount of the fault know it differently and for this type of responsibility, they have determined a certain territory.